Changes in the abundance of keystone forest floor species in response to changes of forest structure. (1st August 2012) - Hedwall, Per‐Ola; Brunet, Jörg; Nordin, Annika; Bergh, Johan
Abstract: Question: Does the abundance of keystone forest floor species change in response to changes in the forest structure? Location: Sweden Methods: We used data from the Swedish National Forest Inventory to investigate changes in the abundance of three common species, as well as the total abundance of all understorey vascular plants (the field layer) in forests in the boreal and temperate parts of Sweden. GLMs and GAMs were used to relate species abundance and temporal changes in abundances to forest structure and forest structural change. Results: Productivity, measured as the site index, was the most important determinant of individual species' abundance. The volume of Picea abies, the density of tree stems and forest age were among the most important forest structural variables. We found that the dwarf shrub Vaccinium myrtillus, the narrow‐leaved grasses (mainly Avenella flexuosa ) and the total field layer cover decreased in boreal Sweden from 1994 through 2010 and that these changes coincided with an increase in forest density and with a reduction in forest age. Conclusions: Changes in Swedish forests to higher tree layer density and younger age appear to contribute significantly to current changes in forest floor vegetation. The use of more intensive thinning practices to reduce the total density of the forest and to increase the proportion of broad‐leaved tree species and Pinus sylvestris would favour the forest floor species in this study. Moreover, increasing forest age (i.e. the length of rotation periods) might favour V. myrtillus in particular, for which the time since disturbance is important for the recovery of pre‐disturbance abundance. However, increased thinning intensity and forest age will reduce the potential for wood production, implying a trade‐off between production of wood and maintenance of well‐developed forest floor vegetation. Abstract : Key‐stone species in the forest floor vegetation have decreased in abundance together with an increase in forest density and a decrease in forest age in boreal Sweden during the last decades. This study shows that forest structure has a strong impact on these species and that the structural changes probably have contributed substantially to the observed changes in species abundance.